Evaluating Patient Satisfaction with Healthcare Services in Government Community Health Centres (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study assessed patient satisfaction with healthcare services at government Community Health Centres (CHCs) in rural areas of Rohtak Division, Haryana. The objectives included evaluating overall satisfaction levels, identifying influencing factors such as medical care quality, staff behavior, infrastructure, and cleanliness, examining the relationship between socio-demographic variables and satisfaction, and providing recommendations for service improvement. A cross-sectional descriptive design was adopted, involving a structured questionnaire administered to 300 patients through purposive sampling. Quantitative data were analyzed using descriptive statistics, regression analysis, chi-square tests, and ANOVA, while qualitative responses underwent thematic analysis.Results showed a high overall satisfaction rate (82%), with medical care quality (85%) and staff behavior (80%) rated highest. Multiple regression analysis revealed medical treatment quality (β=0.38, p<0.001) and staff behavior (β=0.21, p=0.001) as the strongest predictors of satisfaction. Cleanliness, medicine availability, and infrastructure also had significant effects, while waiting time showed a weaker influence. Satisfaction was significantly associated with age, education, and income (p<0.01), but not with gender. Thematic analysis highlighted concerns about waiting times, medicine shortages, and hygiene, leading to practical recommendations such as queue management systems and staff training.The study provides evidence-based insights to enhance service delivery and patient satisfaction in rural government healthcare settings.